Is the extraction by Whatman FTA filter matrix technology and sequencing of large ribosomal subunit D1–D2 region sufficient for identification of clinical fungi?. Issue 10 (21st August 2015) - Kiraz, Nuri; Oz, Yasemin; Aslan, Huseyin; Erturan, Zayre; Ener, Beyza; Arikan Akdagli, Sevtap; Muslumanoglu, Hamza; Cetinkaya, Zafer
Summary: Although conventional identification of pathogenic fungi is based on the combination of tests evaluating their morphological and biochemical characteristics, they can fail to identify the less common species or the differentiation of closely related species. In addition these tests are time consuming, labour‐intensive and require experienced personnel. We evaluated the feasibility and sufficiency of DNA extraction by Whatman FTA filter matrix technology and DNA sequencing of D1–D2 region of the large ribosomal subunit gene for identification of clinical isolates of 21 yeast and 160 moulds in our clinical mycology laboratory. While the yeast isolates were identified at species level with 100% homology, 102 (63.75%) clinically important mould isolates were identified at species level, 56 (35%) isolates at genus level against fungal sequences existing in DNA databases and two (1.25%) isolates could not be identified. Consequently, Whatman FTA filter matrix technology was a useful method for extraction of fungal DNA; extremely rapid, practical and successful. Sequence analysis strategy of D1–D2 region of the large ribosomal subunit gene was found considerably sufficient in identification to genus level for the most clinical fungi. However, the identification to species level and especially discrimination of closely related species may require additional analysis.